NGOs and poverty reduction in Tamil Nadu : exploring a knowledge-sharing for development framework - Langmann, Sten (Curtin University, 2014)
Poverty reduction remains a concern in both a global and Indian context, being a major objective of current development planning processes. The aim of this thesis is to explore an alternative post-colonial approach to the application of knowledge management to development, focussed on the problem of poverty reduction in the context of NGOs operating in Tamil Nadu. A qualitative research design was adopted, drawing on multiple sources of data, collected in Tamil Nadu. It was found that a Knowledge Sharing for Development (KS4D) framework emerged as a way how NGOs can more effectively share knowledge.